Dependencia emocional y su incidencia en la ansiedad en mujeres de la Ciudadela Atalaya del Cantón Echeandía Provincia de Bolívar - Ulloa Viscarra, Shirley Anabely (2023)
The purpose of this research is to describe how emotional dependence affects the anxiety of women in the “Atalaya” citadel of the Echeandía Canton, Province of Bolívar, thus, through the finite sample in a population of 100 women, a result of 53 people, therefore it was evaluated in 53 women through techniques such as interviews and Psychometric Tests, so these techniques allow the collection of information, through the instruments, Beck's Anxiety Test, Emotional Dependency Inventory (IDE ), Open-ended questionnaire. This research is descriptive since through the quantitative and qualitative method it allowed us to collect and verify the data obtained, being favorable for the interpretation of the results. Furthermore, this research is based on a non-experimental design. The results obtained in this research are feasible, allowing the research hypothesis to be exemplified. Therefore, the results were obtained that in the Atalaya citadel women suffer from emotional dependence at a high level and present severe anxiety, thus it was possible to affirm the incidence of emotional dependence on anxiety, since generally the greater the dependence the greater the anxiety.